2021
DOI: 10.32641/andespediatr.v92i2.2794
|View full text |Cite
|
Sign up to set email alerts
|

Trastorno de Evitación y Restricción de la Ingesta de Alimentos (ARFID): Lo que el pediatra debe saber

Abstract: Los problemas en la alimentación durante la infancia han sido descritos a lo largo del tiempo por diversos autores. El diagnóstico de Trastorno de Evitación y Restricción de la Ingesta de Alimentos, (ARFID, de sus siglas en inglés) fue incluido en el Manual Diagnóstico y Estadístico de Trastornos Mentales, 5ta Edición (DSM-5) el año 2013, como un nuevo diagnóstico dentro de los Trastornos Alimentarios y de Ingesta (TAI) para describir un grupo de pacientes que tienen conductas alimentarias evitativas o restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(68 reference statements)
1
5
0
3
Order By: Relevance
“…Current results showed that the occurrence of food neophobia was similar across age groups of adolescents, something higher in boys than in girls, showing just minor differences in taste preferences (sweet, bitter, and umami) between ages, which agrees with previous findings, as well as that food neophobias were slightly higher in boys [10,80,81]. The current results also showed that the older the adolescents were, the higher the acceptance of several foods (grains and tubers and fruits), and the lower of others (vegetables and pulses), despite it being pointed out that food neophobia decreases around the age of five [10], which resulted in the rejection to try new foods as they got older.…”
Section: Discussionsupporting
confidence: 91%
“…Current results showed that the occurrence of food neophobia was similar across age groups of adolescents, something higher in boys than in girls, showing just minor differences in taste preferences (sweet, bitter, and umami) between ages, which agrees with previous findings, as well as that food neophobias were slightly higher in boys [10,80,81]. The current results also showed that the older the adolescents were, the higher the acceptance of several foods (grains and tubers and fruits), and the lower of others (vegetables and pulses), despite it being pointed out that food neophobia decreases around the age of five [10], which resulted in the rejection to try new foods as they got older.…”
Section: Discussionsupporting
confidence: 91%
“…Para lo anterior, Milano et al, han propuesto banderas rojas en distintas áreas, como una de las estrategias para el enfrentamiento de este diagnóstico, que incluyen identificar algún desencadenante del cambio en la conducta alimentaria, así como la presencia de síntomas ansiosos y fóbicos a lo largo de la vida 37 . La detección precoz y psicoeducación parental hacia una alimentación sensible y sobre los efectos de la presión para comer podría disminuir o prevenir dichas conductas alimentarias 1 .…”
Section: Discussionunclassified
“…Reconocer los signos y síntomas de los trastornos alimentarios en la infancia, tanto para su prevención como tratamiento, es una tarea inminente para los profesionales de la salud especialmente dado lo reciente del diagnóstico, falta de estudios y caracterización de estas poblaciones 1 . Recientemente, para mejorar la utilidad clínica en la clasificación de los diagnósticos relacionados con alimentación en la infancia, en base a estudios de campo y opinión de expertos, el DSM-5 rearticuló los trastornos alimentarios de inicio en la infancia con el nombre Trastorno de Evitación/Restricción de la Ingesta de Alimentos (TERIA en castellano, ARFID en inglés).…”
Section: Introductionunclassified
“…The nutritional strategy in selecting dietary intervention should consider the propensity for eating disorders in the form of ARFID (5-22.5% of clinical cases) and PICA (3.5-29% of diagnoses) among the neuropaediatric group. Underlying avoidance and restricted eating are sensory aversions triggered by a particular taste, smell, texture, or shape, followed by a low sensation of hunger, lack of appetite stimulation, and psychological aversions with traumatic and anxiety-related causes [21,22]. Pervasive craving disorder involves the consumption of inedible foods, most often by hiding/homing them in advance, leading to a life-and health-threatening condition for children on the autism spectrum.…”
Section: Nutritional Disorders With An Autism Disorder -Avoidant/rest...mentioning
confidence: 99%